Electron beam sterilization - Nor Rul Hasma, Abdullah (2004)
Nowadays, an automation technology confront with a difficulty in constructing equipments for applications in the highvoltage side. Programmable logic controllers (PLC) and other electronic components for example have to be protected against overvoltages and in the case of electron beam systems also against x-rays. This is expensive and not easy to achieve but possible. The project is consists of three stages. The first stage demonstrates, through experimental on two parts of circuit boards inside the highvoltage deck of electron beam accelerator unit; filament control circuit board and beam control circuit boards. In these circuit boards, an analog signal flow from low / voltage sides via optical link cable to the ground and transmitted to the highvoltage side. The calibrations are made to ensure it's operated correctly. The second stage is to generate a new method of filament control and beam control circuit by constructing a Programmable Logic Controller (PLC) using the STEP 7- Micro/W1N32 and SIMATIC WinCC software provided by SIEMENS AG. It is capable to operate under a highvoltage potential. It uses a PROFJBUS technology as the central connecting link for digital signal flow in the system. The advantages of digital solution are the speed of data transmitting in both directions are faster and better signal to noise ratio (SNR) than analog solution. Finally, as the circuits in both projects are operated under a highvoltage potential, thus there will be a conflict with the transient voltage upon the components, equipments and cables installed in the circuits. Therefore, in the third stage, one circuit protection is created and examined to show transient voltage fault investigation methods and possible solutions. At the end, this project is attempted to expand the automation technology in highvoltage area and support future development in this area